A review on current scenario of Nanocatalysts in biofuel production and potential of organic and inorganic nanoparticles in biohydrogen production. (15th April 2023) - Wu, Yingji; Xia, Changlei; Cao, Jiajie; AL Garalleh, Hakim; Garaleh, Mazen; Khouj, Mohammed; Pugazhendhi, Arivalagan
Graphical abstract: Highlights: Significance of biohydrogen than fossil fuel has been discussed sufficiently. Typical methods reported for biohydrogen production has incorporated. Optimistic contributions and influence of nanoparticles for biohydrogen production. List of organic nanoparticles reported for BHP discussed in detail. Inorganic particles applied for biohydrogen production has been tabulated. Abstract: Biofuel is one of the leading global alternatives to fossil fuels, particularly in the current scenario where energy sources are rapidly depleting. Petroleum fuels endanger both the climate and public health through releasing greenhouse gases during combustion. Nanoparticles acting as catalysts can improve selectivity, quality, and yield with current technology. Biofuel biomasses are abundant, and with improved processing, we may be able to reduce our reliance on fossil fuels significantly. The majority of techniques have recently been implemented, and many nanoparticles such as organic and inorganic metals are now being applied to improve biofuel fabrication. The larger surface area & volume ratio, design, reusability,  catalytic activity, and stability of nanoparticles make them successful biofuel active ingredients. Furthermore, nanoparticles including nanosheets,  carbon nanotubes, and carbon nanofibers have been discovered to really be cost effective and durable catalysts for immobilization of enzyme, thereby enhancing biofuel fabrication in microbes. The incorporation of nanoparticles with in media to replenish the biohydrogen (H2 ) fabrication is considered as a strong and potential approach. The possible impact of nanoparticles in enhancing H2 production in dark and photo-fermentative microbes fed sugars as well as organic wastes substances was investigated in this review. Furthermore, the review provides a comprehensive overview of the use of various nanoparticles in biofuel fabrication, as well as significant challenges and potential future prospects.